The Oxford handbook of gender and conflict - Ní Aoláin, Fionnuala, 1967-; Cahn, Naomi R.; Haynes, Dina Francesca; Valji, Nahla, 1975-
"Traditionally, scholars of war and conflict have focused on men's experiences. Men comprised the armies, and men suffered the most casualties in formal conflicts. In short, gender was rarely considered at all. Yet with the onset of total war in the twentieth century, such a rigidly gendered approach no longer made sense, if it ever did. In virtually every major conflict since the onset of World War II, women suffered enormously. In recent times, scholars of war and conflict have paid far more attention to the role of women in conflict, both as civilians and -occasionally--as participants. But this is not to say that the study of gender and conflict is simply about women. Gender is a two-way street, and the best work on the topic has been cognizant of men, women, and the interactions between men and women. In The Oxford Handbook of Gender and Conflict, Naomi Cahn, Fionnuala Ni Aoilain, and Dina Haynes focus on the multidimensionality of gender in conflict, yet they also prioritize the experience of women given both the changing nature of war and the historical de-emphasis on women's experiences.Operating from this basic intellectual foundation, the editors have arranged the book into seven core sections: the theoretical foundations of the role of gender in violent conflicts; the sources for studying contemporary conflict; the conflicts themselves; the post-conflict process; institutions and actors; the challenges presented by the evolving nature of war; and, finally, a substantial set of case studies from across the globe. Genuinely comprehensive, this volume will not only serve as an authoritative overview of this massive topic, it will set the research agenda for years to come"--